An overview of fish fauna of Raigad District, northern Western Ghats, India - Unmesh Katwate; Rupesh Raut; Sahir Advani (Journal of Threatened Taxa, 2012)
We studied the fish fauna of Raigad District for two years from August 2008 to August 2010. Sixty six freshwater and secondary freshwater fish species belonging to 31 families and 53 genera were collected from various sampling sites and local markets along the banks of Patalganga, Bhogawati, Amba, Kundalika, Mandad and Savitri river systems present in Raigad District, Maharashtra, northern Western Ghats. Cyprinids were the most dominant group represented by 22 fish species belonging to 13 genera followed by the loaches, croakers and gobies belonging to the family Balitoridae, Sciaenidae and Gobiidae respectively (three species from each family). Of the 66 fish species, five belong to the Vulnerable (VU), four to Near Threatened (NT), 37 to the Least Concern (LC) category and 20 were found to be not evaluated for IUCN Red List criteria. Raigad District is under severe threat of rapid industrialization and urbanization. Further, introduced exotic fish species are becoming a major threat to the indigenous fish fauna of Raigad District. Implementation of ecosystem based adaptation plans and conservation measures are necessary to protect the diverse, endemic and threatened fish fauna of Raigad District.